2012
DOI: 10.1038/ng.2205
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of gene expression in primary immune cells identifies cell type–specific master regulators and roles of HLA alleles

Abstract: Trans-acting genetic variants play a substantial, albeit poorly characterized, role in the heritable determination of gene expression. Using paired purified primary monocytes and B-cells we identify novel, predominantly cell-specific, cis- and trans-eQTL (expression quantitative trait loci). These include multi-locus trans-associations to LYZ in monocytes and to KLF4 in B-cells. Additionally, we observe B-cell specific trans-association of rs11171739 at 12q13.2, a known autoimmune disease locus, to IP6K2 (pB-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
513
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 461 publications
(578 citation statements)
references
References 69 publications
37
513
5
2
Order By: Relevance
“…Recently lysozyme (LYZ) on chromosome 12q15 has been described as a monocyte-specific master regulator eQTL 20 . In this study, rs10784774 was identified as cis eQTL for LYZ and as trans eQTL for 62 other genes under baseline condition.…”
Section: δLps/baselinementioning
confidence: 99%
“…Recently lysozyme (LYZ) on chromosome 12q15 has been described as a monocyte-specific master regulator eQTL 20 . In this study, rs10784774 was identified as cis eQTL for LYZ and as trans eQTL for 62 other genes under baseline condition.…”
Section: δLps/baselinementioning
confidence: 99%
“…We have reported genomewide expression quantitative trait (eQTL) analysis in different primary human cell populations [24]. This global analysis included evidence of a local, cis-eQTL involving CIITA that was specific to B cells.…”
Section: Insights From the Genetical Genomics Of Ciitamentioning
confidence: 99%
“…28 Moreover, several SNPs in human leukocyte antigen (HLA) genes have been found with the susceptibility of protection of development of NAbs responses. 29,30 Considering all the facts, it is still premature to achieve consensus about the limiting role of NAbs against IFN-β therapy in clinics and, therefore, the evaluation of NAbs in practice is not yet completely applicable.…”
Section: Pharmacogenomic Investigational Strategiesmentioning
confidence: 99%